PECULIARITIES OF PROFESSIONAL TRAINING OF FUTURE FOREIGN ECONOMIC AIRLINE ACTIVITY MANAGERS AT THE HIGHER FLYING EDUCATIONAL INSTITUTIONS - Крилова, К. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is devoted to consideration of such an urgent topic as training of future foreign economic airline activity managers in flying educational institutions. The professionally significant qualities, competences, which must be possessed by the manager of foreign economic activity, determination and components of the communicative competence of the future foreign economic activity managers are considered